Nigerian Construction Industry Reforms and Private Sector Involvement: X-raying Cost Engineering Roles in Sustainable Infrastructure Procurement - Amadi Alolote Ibim; Kelechukwu Dimkpa (Journal of Evrímata: Engineering and Physics, 2025)
This study examines the essential financial oversight cost engineering functions performed in the procurement of sustainable infrastructure. This is against the backdrop of the Nigerian construction industry, which has undergone significant transformation through targeted government policies and reforms, aimed at addressing procurement gaps and enhancing infrastructure development. As a result, innovative procurement methods have been adopted to ensure sustainability in public infrastructure projects. Cost engineering and financial management functions are necessary to ensure fiscal accountability in public project procurement. A systematic review of the extant literature is carried out to x-ray cost engineering roles in sustainable infrastructure procurement. Findings indicate a shift from a predominantly public sector-led approach to one driven by private investment, presenting new opportunities for cost engineering roles. Cost engineering expertise is needed in contract administration, risk mitigation, and financial planning and is instrumental in optimizing Public-Private Partnership (PPP) agreements and ensuring long-term project viability. The study underscores the need for Quantity Surveyors, who are professionally skilled in carrying out cost engineering functions, to strategically position themselves within the evolving procurement landscape to leverage emerging opportunities. This study therefore underscores the importance of diversification, and adaptability in navigating industry shifts in the cost management of public infrastructure projects. By embracing these principles, cost engineering roles will maintain relevance in sustainable infrastructure development. There is thus a need to strengthen the connection between government policies, innovative procurement methods, with a view to catalyse cost engineering functions, and their impact in sustainable infrastructure development.